Presence in the blood of cheirópteros Lima, Trypanosoma Vespertilonis (Battaglia, 1904) - Noriega del Aguila, M. (1919)
Examining the fresh blood of several species of cheirópteros the molossus gender, in order to know the percentage of these mammals parasitized are a microfilaria, previously found (unpublished work), we had the chance of finding 22 May 1917 vespertilionis trypanosome (Battaglia, 1904), as we described, for the references, you have not been with us and that their identification is indisputable, after the study of fresh and stained preparations the state of the photomicrographs and drawings which I enclose.